Psychological Safety and Employee Voice in IT Sector: Parallel Mediation Effect of Affective Commitment and Intrinsic Motivation - Soumyaja, Devi; Kuriakose, Jeeva (Ushus Journal of Business Management, 2020)
The study is an attempt to explain the relationship of psychological safety on employee voice behaviour by examining the mediating role of affective commitment and intrinsic motivation. A questionnaire was distributed amongst 161 IT professionals through convenience sampling. Mediation Analysis was used to find the effect of the mediators in influencing the relationship between psychological safety and prosocial voice. The result suggested psychological safety is parallelly mediated by both affective commitment and intrinsic motivation, leading to employee prosocial voice. Intrinsic motivation was found to have a greater mediating effect than affective commitment.